Uji Efektivitas Ekstrak Serai (Cymbopogon citratus) terhadap Penyembuhan Luka Sayat pada Mencit Putih - Maharuni Nurqadriasti Djuddawi; Haryati Haryati; Andi Noor Kholidha (Jurnal Surya Medika (JSM), 2019)
The wound is an injury to the part of the body where the skin and underlying tissues lose its tissue continuity. Lemongrass is one of the grass plants that often used as a medicine that can function as an antibacterial, anti-inflammatory, and antioxidant that can affect the wound healing process. This study aims to evaluate the effectiveness of lemongrass extract (Cymbopogon citratus) on wound healing in white mice. This research is true experimental research with a post-test only control group design. This research used 25 white mice divided into 5 groups: 30% lemongrass extract, 60% lemongrass extract, 80% lemongrass extract, negative control (Aquades) and positive control (Bioplacenton). The grouping of subjects was carried out randomly. Normality test using the Shapiro Wilk test shows the p-value in each group > 0.05, it can be concluded that the data distribution is normal. Levene's Test homogeneity test was obtained p-value = 0.730 (p> 0.05), thus the data variant is homogeneous. The results of the analysis with One-Way ANOVA test showed p-value = 0.881 (p > 0.05). There was no difference in the effectiveness of lemongrass extract (Cymbopogon citratus) 30%, 60%, and 80% compared to negative control groups and positive control of wound healing in white mice. However, wound healing in the 60% lemongrass extract group was faster and total wound healing had occurred on the 14th day. Wound healing is slowest in the 80% lemongrass extract group.